2021
DOI: 10.1007/s10571-021-01085-4
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-499a-5p Decreases Cerebral Ischemia/Reperfusion Injury by Targeting PDCD4

Abstract: MiR-499a-5p was signi cantly down-regulated in degenerative tissues and correlated with apoptosis.Nonetheless, the biological function of miR-499a-5p in acute ischemic stroke has been still unclear. In this study, we found the plasma levels of miR-499a-5p were signi cantly down-regulated in 64 ischemic stroke patients and negatively correlated with the National Institutes of Health Stroke Scale score. Then, we constructed cerebral ischemia/reperfusion (I/R) injury in rats after middle cerebral artery occlusion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…PDCD4 facilitated lung tumor cell apoptosis by inhibiting p62-Nrf2 signaling pathway and up-regulating Keap1 expression ( 44 ). After the expression of PDCD4 was inhibited by miR-499a-5p, neuronal apoptosis decreased in ischemic brain injury ( 45 ). In this study, we found that miR-93-5p overexpression significantly reduced the expression of PDCD4, which inhibited the apoptosis of AOH retinal neurons ( Figs 2 – 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…PDCD4 facilitated lung tumor cell apoptosis by inhibiting p62-Nrf2 signaling pathway and up-regulating Keap1 expression ( 44 ). After the expression of PDCD4 was inhibited by miR-499a-5p, neuronal apoptosis decreased in ischemic brain injury ( 45 ). In this study, we found that miR-93-5p overexpression significantly reduced the expression of PDCD4, which inhibited the apoptosis of AOH retinal neurons ( Figs 2 – 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our result presented with elevated concentrations of CK-MB and BNP while the concentrations of SOD and COX IV were reduced in LPS-treated AC16 cells, whereas an overexpression of miR-499a-5p could invert the findings. Shan et al have implicated miR-499a-5p upregulation in the mitigation of cerebral I/R injury [ 37 ]. Similarly, our result elicited that miR-499a-5p overexpression alleviated SIMD.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have revealed that PDCD4 knockout can reduce the chronic stress-induced depression-like behavior in mice ( 14 ), whereas increased PDCD4 levels in vitro can lead to significant reductions in axonal length ( 15 ). In addition, PDCD4 knockdown has been observed to reduce infarct damage and cortical neuronal apoptosis induced by brain ischemia/reperfusion injury ( 16 ).…”
Section: Introductionmentioning
confidence: 99%